Geometry and Material Constraint Effects on Creep Crack Growth Behavior in Welded Joints - Li Y.; Wang G. Z.; Xuan F. Z.; Tu S. T. (High Temperature Materials and Processes, 2017)
In this work, the geometry and material constraint effects on creep crack growth (CCG) and behavior in welded joints were investigated. The CCG paths and rates of two kinds of specimen geometry (C(T) and M(T)) with initial cracks located at soft HAZ (heat-affected zone with lower creep strength) and different material mismatches were simulated. The effect of constraint on creep crack initiation (CCI) time was discussed. The results show that there exists interaction between geometry and material constraints in terms of their effects on CCG rate and CCI time of welded joints. Under the condition of low geometry constraint, the effect of material constraint on CCG rate and CCI time becomes more obvious. Higher material constraint can promote CCG due to the formation of higher stress triaxiality around crack tip. Higher geometry constraint can increase CCG rate and reduce CCI time of welded joints. Both geometry and material constraints should be considered in creep life assessment and design for high-temperature welded components.